Human 15‐lipoxygenase‐1 is a regulator of dendriticcell spreading and podosome formation. Issue 2 (17th October 2016) - Han, Hongya; Liang, Xiuming; Ekberg, Monica; Kritikou, Joanna S.; Brunnström, Åsa; Pelcman, Benjamin; Matl, Maria; Miao, Xinyan; Andersson, Margareta; Yuan, Xiaotian; Schain, Frida; Parvin, Selina; et al.
ABSTRACT: Dendritic cells (DCs) involved in proinflammatory immune responses derive mainly from peripheral monocytes, and the cells subsequently mature and migrate into the inflammatory micromilieu. Here we report that suppressing of 15‐lipoxygenase‐1 led to a substantial reduction in DC spreading and podosome formation in vitro. The surface expression of CD83 was significantly lower in both sh‐15‐lipoxygenase‐1 (15‐LOX‐1)‐transduced cells and DCs cultivated in the presence of a novel specific 15‐LOX‐1 inhibitor. The T‐cell response against tetanus‐pulsed DCs was only affected to a minor extent on inhibition of 15‐LOX‐1. In contrast, endocytosis and migration ability of DCs were significantly suppressed on 15‐LOX‐1 inhibition. The expression of 15‐LOX‐1 in DCs was also demonstrated in affected human skin in atopic and contact dermatitis, showing that the enzyme is indeed expressed in inflammatory diseases in vivo. This study demonstrated that inhibiting 15‐LOX‐1 ledtoanimpairedpodosome formation in DCs, and consequently suppressed antigen uptake and migration capacity. These results indicated that 15‐LOX‐1 is a potential target for inhibiting the trafficking of DCs to lymphoid organs and inflamed tissues and decreasing the inflammatory response attenuating symptoms of certain immunologic and inflammatory disorders such as dermatitis.—Han, H., Liang, X., Ekberg, M., Kritikou, J. S., Brunnström, Å., Pelcman, B., Matl, M., Miao, X., Andersson, M., Yuan, X., Schain, F., Parvin, S., Melin, E., Sjåberg, J., Xu, D., Westerberg, L. S., Bjårkholm, M., Claesson, H.‐E. Human 15‐lipoxygenase‐1 is a regulator of dendritic‐cell spreading and podosome formation. FASEB J. 31, 491–504 (2017). www.fasebj.org